2006
DOI: 10.1111/j.1530-0277.2006.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Motor Delays in Young Children With Fetal Alcohol Syndrome to Those With Prenatal Alcohol Exposure and With No Prenatal Alcohol Exposure

Abstract: These findings strongly suggest that all young children with FAS should receive complete developmental evaluations that include assessment of their motor functioning, to identify problem areas and provide access to developmental intervention programs that target deficit areas such as fine motor skills. Fine motor delays in children with FAS may be related to specific neurobehavioral deficits that affect fine motor skills. The findings support the concept of an FASD continuum in some areas of motor development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 30 publications
2
66
1
Order By: Relevance
“…21 One implication concerning these critical periods is that, if a pregnant woman has limited or no access to alcohol during weeks 3 and 4, for instance, her child may lack the facial dysmorphologic features but still have serious neurologic damage from later alcohol exposure. The significantly higher neuromotor deficiency scores found for the children with FAS were observed in earlier studies of FAS 22,23 and in a French study in which heavy maternal alcohol consumption (Ͼ21 drinks a week) was associated specifically with higher neuromotor deficiency scores. 24 This underscores the significant prenatal alcohol exposure in these adoptees.…”
Section: Figurementioning
confidence: 60%
“…21 One implication concerning these critical periods is that, if a pregnant woman has limited or no access to alcohol during weeks 3 and 4, for instance, her child may lack the facial dysmorphologic features but still have serious neurologic damage from later alcohol exposure. The significantly higher neuromotor deficiency scores found for the children with FAS were observed in earlier studies of FAS 22,23 and in a French study in which heavy maternal alcohol consumption (Ͼ21 drinks a week) was associated specifically with higher neuromotor deficiency scores. 24 This underscores the significant prenatal alcohol exposure in these adoptees.…”
Section: Figurementioning
confidence: 60%
“…Further neurobehavioral difficulties include neurological signs, such as kinetic tremors, weak grasp, seizures, and hypotonia (Spohr et al, 1993), while studies of motor development and motor skills have described motor incoordination (Roebuck-Spencer et al, 2004), difficulty with eye-hand coordination (Adnams et al, 2001), and poor balance (Barr et al, 1990), as a result of prenatal alcohol exposure. Studies in infants and children exposed prenatally to alcohol have demonstrated motor performance deficits and impaired development of both fine and gross motor skills (for review, see Autti-Ramo and Granstrom, 1991;Kalberg et al, 2006;Osborn et al, 1993). However, the field lacks specificity regarding the type of motor problems that are characteristic of FASD and information relating to the underlying neurophysiological mechanisms.…”
mentioning
confidence: 98%
“…FASD affects 0.3 to 10 individuals per 1000 live births (May and Gossage, 2001), and is the leading cause of preventable mental retardation (Abel and Sokol, 1986). Children with FASD show widespread structural brain abnormalities (Archibald et al, 2001;Fryer et al, 2009;Lebel et al, 2008;Mattson et al, 1996), and may have various cognitive and behavioral impairments including motor delays, and deficits of attention, executive functioning, language, learning, and memory (Jacobson and Jacobson, 2002;Kalberg et al, 2006;Mukherjee et al, 2006;Spadoni et al, 2007). Despite an array of intellectual impairments, individuals with FASD generally have greater difficulty with arithmetic than other cognitive domains (Howell et al, 2006;Kopera-Frye et al, 1996;Rasmussen and Bisanz, 2009) and mathematical ability is more strongly correlated with amount of prenatal alcohol exposure than are other academic skills (Goldschmidt et al, 1996;Streissguth et al, 1994).…”
mentioning
confidence: 98%